Evaluation of the impacts of end-of-life management strategies for deconstruction of a high-rise concrete framed office building. (1st January 2017) - Chau, C.K.; Xu, J.M.; Leung, T.M.; Ng, W.Y.
Highlights: Energy savings obtained from various EOL management strategies were estimated. Recycling aluminum and external walls achieved the highest energy saving. Maximum reuse could save up to 38.5% of the total embodied energy of original buildings. The best EOL management strategies varied with types of materials and their life spans. Abstract: Recently, greater attentions have been started to put on the end-of-life (EoL) phase of buildings. Recycling, reuse and incineration of deconstructed wastes can help relieve the landfill burden and recover some energy from existing building materials in order to reduce environment impacts and/or reduce energy consumption. Life cycle energy assessment (LCEA) was performed for the EoL phase of a high-rise concrete office building in Hong Kong. The amount of energy that could be saved at the EoL phase through implementation of a specific EoL management strategy was evaluated in terms of energy saving potential (ESP), which was defined as the percentage of energy savings from the salvage materials to the total embodied energy of the building during its initial construction. Recycling of aluminum (30.7% ESP) and recycling of external walls (30.6% ESP) contributed to most of the total energy saving. Maximum reuse provided higher energy savings than maximum recycling (38.5% vs 35.9% ESP), while maximum incineration was not able to bring any energy saving (−44.8% ESP). In addition, the best EoL management strategies for different materials and elements were found to vary with time after taking the remaining proportions of embodied energy into considerations. Implementing the best EoL management strategies for different materials gave an ESP of 54.4% for 50-year life span. The life span of a building exerted considerable influences on the amount of energy saving. Highest energy saving was gained by implementing the best EoL strategies for 70-year life span.